Integrative RAPD and SSR marker analysis reveals genetic diversity associated with fruit shape variation in pepper (Capsicum spp.) - ‘AINUN SAYYIDAH ZAKIYAH; DIAN SISWANTO; DWINITA WIKAN UTAMI; ESTRI LARAS ARUMINGTYAS (Society for Indonesian Biodiversity, 2026)
Abstract. Zakiyah ‘AS, Siswanto D, Utami DW, Arumingtyas EL. 2026. Integrative RAPD and SSR marker analysis reveals genetic diversity associated with fruit shape variation in pepper (Capsicum spp.). Biodiversitas 27 (4): d270422. https://doi.org/10.13057/biodiv/d270422. The shape of pepper (Capsicum spp.) fruit significantly influences consumer preferences, which, in turn, affects its commercialization and economic value. In nature, peppers exhibit a wide range of fruit shapes that may be caused by genetic or environmental factors. Information confirming the causal factors underlying this variation, particularly at the molecular level, remains limited. Molecular markers are essential tools for assessing genetic diversity within germplasm. This research aims to identify the genetic profiles of pepper with various fruit shapes using RAPD and SSR markers. The findings will be beneficial for future studies concerning the genetic mechanisms underlying fruit shape in peppers. The study examined ten Capsicum spp. genotypes characterized by elongated, triangular, and blocky fruit shapes. A total of nineteen RAPD and seventeen SSR markers were employed for analysis. The data were processed using the UPGMA method based on Jaccard’s similarity coefficient for RAPD, and Euclidean similarity coefficient for SSR. The results from both RAPD and SSR markers indicated polymorphism in alleles. Specifically, OPU-10 and Chr12SSR10 show higher polymorphism, as indicated by PIC values. The dendrogram generated from both markers demonstrated that the clustering was closely related to fruit morphology, particularly in distinguishing elongated, triangular, and blocky fruit shapes. The RAPD and SSR markers are reliable for identifying genetic diversity in Capsicum spp. Specifically, the OPU-10 and Chr12SSR10 markers may have potential for future studies on genetic diversity related to fruit morphology.